2017
DOI: 10.1149/2.0291708jes
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Solid Al2O3with Electrolysis of CaCl2-Based Melt

Abstract: Cyclic and square-wave voltammetry methods are used to investigate the mechanism of the cathode process on molybdenum in a CaCl 2 -CaF 2 melt at 750 • C. It is shown that calcium reduces on an inert cathode in the form of its solution in catholyte at potentials more positive than are required for metallic calcium formation. The presence of Al 2 O 3 in the catholyte increases currents of calcium reduction on the forward cathodic wave at potentials more positive than are required for metallic calcium formation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Similar polarization dependencies with the rapid consumption of reduced forms were obtained earlier. 33,34 The potassium electrowinning was not achieved at low sweep rates, whereas the typical slow discharge wave K of the potassium electrowinning at potential negatively than −1.3 V was obtained at high sweep rates.…”
Section: Resultsmentioning
confidence: 99%
“…Similar polarization dependencies with the rapid consumption of reduced forms were obtained earlier. 33,34 The potassium electrowinning was not achieved at low sweep rates, whereas the typical slow discharge wave K of the potassium electrowinning at potential negatively than −1.3 V was obtained at high sweep rates.…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24][25][26][27] In addition, the direct electroreduction of solid Al 2 O 3 has also been investigated in different molten salts, such as CaCl 2 -NaCl, CaCl 2 -LiCl, and CaCl 2 -CaF 2 . [28][29][30] Noteworthily, Al has a low melting point of 660 • C, which means that formed Al is liquid when the electrolysis was carried out at a higher temperature (such as 900 • C). In order to overcome this z E-mail: xzou@utexas.edu; luxg@shu.edu.cn drawback, the mixed oxides can be used as the precursor to directly synthesize refractory alloys, such as Ti-6Al-4Al.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Fray et al reported the direct electrolytic reduction of TiO 2 pellets in a CaCl 2 -based melt, known as the FFC Cambridge process. [1][2][3][4][5][6] This process has the potential to replace the conventional Kroll process for producing Ti metal, owing to its simple system and relatively low temperature.…”
mentioning
confidence: 99%
“…Meanwhile, electrolytic reductions of various kinds of solid oxides in CaCl 2 and/or CaCl 2 -based molten salts have been investigated by many researchers in the last two decades. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Fray et al reported the direct electrolytic reduction of TiO 2 pellets in a CaCl 2based melt, known as the FFC Cambridge process. [1][2][3][4][5][6] This process has the potential to replace the conventional Kroll process for producing Ti metal, owing to its simple system and relatively low temperature.…”
mentioning
confidence: 99%
See 1 more Smart Citation